Tolerance on campus: the impact of religious commitment and respect among university students - Mohammad Jaber Thalgi; Nader Al-Refai; Kadir Gömbeyaz; Hanan Bdoor; Ayse Zisan Furat (International Journal of Evaluation and Research in Education (IJERE), 2026)
Religious commitment, particularly within Islamic contexts, is often viewed as a guiding framework for promoting values such as tolerance, respect, and social harmony; however, differing interpretations and personal expressions of religiosity can sometimes challenge these ideals, necessitating deeper exploration of how religiosity influences social interactions. The study investigates the relationship between religious commitment and respect for others regarding the levels of tolerance behavior among university students. The study employed a descriptive quantitative cross-sectional survey from June 16 to August 16, 2023, with a sample of 334 enrolled in the College of Sharia at Yarmouk University in Jordan. The survey consists of three main scales: religious commitment, respect for others, and tolerance. Students’ demographic data, including gender, nationality, age group, academic department, and the year of study, were also collected via the questionnaire. The findings highlight significant gender differences in religious commitment, with males demonstrating higher levels than females. While no significant age differences were observed in religious commitment, tolerance varied notably, particularly among the 24-26 age group. The study participants represented a diverse range of countries of origin. A country-wise analysis revealed that students from Thailand have the highest religious commitment, underscoring the influence of cultural contexts. Departmental comparisons showed no significant differences, although the findings highlight that respect for others impacts tolerance, religious commitment and demography have almost no effect as predicted. The findings emphasize the primary role of respect in fostering social harmony, suggesting that future interventions should focus on promoting respect as a fundamental value in Islamic culture to enhance tolerance.